2020
DOI: 10.1088/1757-899x/810/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Applications and challenges of arc welding methods in dissimilar metal joining

Abstract: Dissimilar metal welding is a significant metal joining process with an extensive application in industrial domain. The quality of the welded joint is of critical importance in these applications and quite an issue since the base metals are different primarily due to different physical, chemical and mechanical characteristics. In this paper, the challenges encountered in dissimilar metal joining are enlisted with a brief discussion on the corresponding causes. As discussed in the literature, several methods ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Previous studies on the TIG welding of diverse and dissimilar metals can be split into three categories: characterization, parameter optimization, and application. Heat conduction from the molten weld pool to a base metal with a higher thermal conductivity absorbs thermal energy and determines the amount of energy needed to melt the base metal locally [9,10]. During cooling, the differing base metals' thermal expansion coefficients produce tensile in one part and compressive stress in the other part.…”
Section: Literature Review 21 Consideration During Welding Dissimilar...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the TIG welding of diverse and dissimilar metals can be split into three categories: characterization, parameter optimization, and application. Heat conduction from the molten weld pool to a base metal with a higher thermal conductivity absorbs thermal energy and determines the amount of energy needed to melt the base metal locally [9,10]. During cooling, the differing base metals' thermal expansion coefficients produce tensile in one part and compressive stress in the other part.…”
Section: Literature Review 21 Consideration During Welding Dissimilar...mentioning
confidence: 99%
“…During cooling, the differing base metals' thermal expansion coefficients produce tensile in one part and compressive stress in the other part. If the stress is not relieved, the metal deposited under tensile stress may experience hot cracking during welding or cold cracking during service [9,10]. When welding metals with significantly different thermal conductivity, the heat source must provide a thermal differential for proper thermal equilibrium.…”
Section: Literature Review 21 Consideration During Welding Dissimilar...mentioning
confidence: 99%
See 1 more Smart Citation
“…Originally FAHP Key criteria and sub-criteria previous research, decision-making A comparison of results and findings among four other multi-attribute decision makers (MADM) sensitivity analysis and proposed methods framework Final ranking procedures and significance criteria show Findings and ensuring credibility. For this purpose, epiphysis the kings weight of inch scales on the Final ranking of Fuzzy ARAS method is analyzed separately [4]. It is successfully used in many Sectors like sustainable development and construction.…”
Section: Fuzzy Arasmentioning
confidence: 99%
“…e austenitic stainless steel and nickel-based alloy with excellent high-temperature mechanical properties and corrosion resistance have been widely used for structural welding materials in nuclear power plant's (NPP) primary circuits [1][2][3][4]. Previous research and practices have shown that corrosion resistance is mainly due to the formation of chromium-rich oxide film on the metal surface.…”
Section: Introductionmentioning
confidence: 99%